Effects of smartphone addiction on cognitive function and physical activity in middle-school children: a cross-sectional study - Al-Amri, Ahlam; Abdulaziz, Sahar; Bashir, Shahid; Ahsan, Mohammad; Abualait, Turki (Frontiers in Psychology, 2023)
Introduction This study aimed to investigate the effects of smartphone addiction on cognitive function and physical activity in middle-school children. Methods A population of 196 children (boys and girls) from middle schools were recruited for this study with an average age of 12.99 ± 0.81 years, a height of 153.86 ± 6.50 meters, a weight of 48.07 ± 7.31 kilograms, and a body mass index of 20.22 ± 2.08 kg/m2. Smartphone addiction was determined using Arabic versions of the Smartphone Addiction Scale-Short Version, and physical activity levels were assessed by a physical activity questionnaire for older children. The working memory and selective attention domains of cognitive function were evaluated using a laptop screen's digital version of the memory automaticity and Flanker tasks, respectively. A one-way MANOVA was conducted to determine the differences in working memory between the smartphone-addicted and non-addicted groups. The relationship between smartphone addiction and physical activity was analyzed using Pearson's chi-squared test. Results The cognitive function-attention domain accuracy component showed a statistically significant difference between the groups, with a p-value of 0.05). The reaction time between smartphone-addicted and non-addicted children showed no statistically significant difference (p = 0.817). The relationship between smartphone addiction and physical activity was statistically significant (p < 0.001). Discussion The interaction effects between physical activity and smartphone addiction on reaction times showed statistically insignificant (p = 0.25) differences, showing that physical activity's effect on reaction times did not depend on smartphone addiction levels. The non-addicted children had significantly higher physical activity levels than the addicted children, indicating that smartphone addiction reduced physical activity.